Experimental Tests on a Spoke-Type Permanent Magnets Synchronous Machine for Light Electric Vehicle Application - Stefan Breban; Marius Dranca; Mihai Chirca; Alexandru-Madalin Pacuraru; Petre-Dorel Teodosescu; Claudiu-Alexandru Oprea (Applied Sciences, 2022)
In an attempt to limit the effects of global warming, virtually all car manufacturers have introduced in the last years Hybrid or full Electric Vehicles. The current study shows the experimental testing of a spoke-type PMSM that was developed based on the requirements of the L6e European light vehicle class. A test bench was developed for this purpose, using a DC machine fed by a bidirectional DC Power Supply that allowed the testing of the PMSM prototype both in motor and generator/brake regimes. The Worldwide Harmonized Light-Duty Vehicles Test Procedure (WLTP) was implemented on the control stage of the testing set-up, allowing an accurate estimation of the PMSM-based E-drivetrain performance. The test results validated the FEM-simulated results and provided an insight on the efficiency of the entire drive system (battery–inverter–PMSM) and the autonomy of the L6e light EV. The electric drive system was integrated and tested on a prototype vehicle in normal operating conditions, validating the results obtained on the developed test bench.